2021
DOI: 10.48550/arxiv.2108.13970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum Fisher Information Bounds on Precision Limits of Circular Dichroism

Jiaxuan Wang,
Girish S. Agarwal

Abstract: Circular dichroism (CD) is a widely used technique for investigating optically chiral molecules, especially for biomolecules. It is thus of great importance that these parameters be estimated precisely so that the molecules with desired functionalities can be designed. In order to surpass the limits of classical measurements, we need to probe the system with quantum light. We develop quantum Fisher information matrix (QFIM) for precision estimates of the circular dichroism and the optical rotary dispersion for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
(52 reference statements)
2
2
0
Order By: Relevance
“…2004; Wang and Agarwal, 2021). The QFIM for this measurement has recently been calculated and shown to outperform that of coherent states, especially in the small-absorption regime (Wang and Agarwal, 2021), similar to other attenuation measurement results.…”
Section: Ellipsometrysupporting
confidence: 77%
See 2 more Smart Citations
“…2004; Wang and Agarwal, 2021). The QFIM for this measurement has recently been calculated and shown to outperform that of coherent states, especially in the small-absorption regime (Wang and Agarwal, 2021), similar to other attenuation measurement results.…”
Section: Ellipsometrysupporting
confidence: 77%
“…2004; Wang and Agarwal, 2021). The QFIM for this measurement has recently been calculated and shown to outperform that of coherent states, especially in the small-absorption regime (Wang and Agarwal, 2021), similar to other attenuation measurement results. Then, the ultimate quantum limit for such a measurement was studied by Rudnicki et al (2020), where it was found that certain squeezed states allow for a simultaneous estimate of both ellipsometry parameters that approaches the Heisenberg limit.…”
Section: Ellipsometrysupporting
confidence: 77%
See 1 more Smart Citation
“…Following the method discussed in [44], we solve the equations for the individual components separately. In other words, the corresponding SLD gets split as…”
Section: The Quantum Cramér-rao Bound For Sensitivitymentioning
confidence: 99%